AN INVESTIGATION INTO THE INTERVENTION STRATEGIES IMPLEMENTED BY EDUCATORS IN ENHANCING LEARNERS’ UNDERSTANDING OF NUMBER SENSE - Hove, Netsai; Hendricks, Winston; Olawale, Babawande Emmanuel (JOHME: Journal of Holistic Mathematics Education, 2023)
Global and country-specific mathematics performance constitutes a major challenge, both for educators and policymakers. Realisation of the African Union Agenda 2013 hinges significantly upon transformation of education. In this regard, mathematics and science education, specifically, are instruments for scientific and technological development to position Africa on the same level as the global league of continents in the future. It is, therefore, important to develop amongst learners a good understanding of a mathematical concept such as number sense from an early age, given that students who have a good sense of numbers can manipulate figures to simplify calculations and have the confidence to approach problems in a variety of ways. It is for this reason that the present study investigates the intervention strategies implemented by educators in enhancing learners’ understanding of number sense in the Ekurhuleni North District schools, Gauteng Province, South Africa. The study used a case study design and a qualitative research approach, both of which were supported by an interpretivist paradigm. The study made use of a semi-structured interview to gather data from mathematics teachers, learners, and a principal in the selected school. Research findings revealed that although mental computation, use of concrete props, use of the number line, and a counting strategy are some of the various strategies employed to enhance learners’ understanding of number sense, teachers need to develop a sound understanding of number sense and be flexible in their approaches in order to assist learners. Based on the findings, it was recommended that curriculum designers and teachers concentrate on teaching methods to help students develop learners’ number sense, as this can lead to potential mathematics success.